Research on Energy-absorbing Structures for Two Endsof High-speed Train Car Body - ZHANG Zhi-xin; TIAN Ai-qing; CHE Quan-wei; XIAO Shou-ne (机车电传动)
Based on high-speed and large-kinetic-energy characteristics of high-speed trains, a special passive protective end energyabsorbing structure was designed and simulated through non-linear finite element software LS-DYNA. The two-step energy-absorbing device fixed on the two cab end as well as low stiffness structure of car body rear end were studied and focused on the interface force, deformation and energy absorption capacity when a collision accident happened. It was proved that the two-step structure deformed orderly and had an energy absorbing capacity of 3.4 MJ, which could protect the cab effectively, and the rear end low stiffness zone had an energy-absorbing capacity of 6.5 MJ, which could protect the integrity of the passenger area. According to EN15227, a train-to-train crash scenario with a relative speed of 36 km/h was simulated and verified. It was proved that trains with energy-absorbing structure mentioned above could meet the need of EN15227 without climbing and damage of living space for both of drivers and passengers. Meanwhile, the average deceleration of the cab car was 4.4g.